The Influence of Lifestyle, Product Quality, and Social Media Marketing Promotion on Purchase Decisions at Lain Hati Coffee Café - Hukmu Adam Mulawarman; Ririn Wulandari (Sultan Publisher, 2025)
This study aims to examine and analyze the Influence of Lifestyle, Product Quality, and Social Media Marketing Promotion on Purchasing Decisions at Cafe Kopi Lain Hati. The independent variables consist of Lifestyle, Product Quality, and Social Media Marketing Promotion. The dependent variable is Purchasing Decision of consumers of Kopi Lain Hati. The population in this study were consumers of Kopi Lain Hati in West Jakarta. The sample was 140 respondents. The data analysis technique used in this study was the Component or Variance Based Structural Equation Model. Hypothesis testing is shown from the inner model, where the instrument test was previously carried out. Data were collected by distributing questionnaires to consumers and processed using the Smart PLS 3.0 program. The results of this study are that Lifestyle has a positive and significant effect on purchasing decisions, Product Quality has a positive and significant effect on purchasing decisions, and Social Media Promotion has a positive and significant effect on purchasing decisions. The results of the study are used as a basis for compiling marketing strategies, especially at Cafe Kopi Lain Hati, as well as marketing strategies for similar companies.